Photographical Assessment of Face Pleasantness using Facial Analysis for a Sample of Iraqi Adults Females (Retrospective Study) - Shahbaa A. Mohammed (Journal of Global Pharma Technology, 2016)
Aims: The aim of this study was to assess facial attractiveness and to check if the numeric facial analysis can determine this attractiveness for a sample of Iraqi adults' females and characterize the studied sample according to subjective concepts of facial esthetics in esthetically pleasant, esthetically acceptable and esthetically unpleasant, considering frontal photographs.  Subjects and Methods: Forty frontal standardized photograph of females aged between 20 and 22 years old. The frontal photograph and lateral photograph were obtained by asking each female to look to the center of the lens and at a distant mirror respectively which is placed in front of her face. All the frontal photographs were evaluated by using our own esthetics criteria (orthodontist evaluation) as graduation in: pleasant, acceptable and not pleasant. The numeric facial analysis was then performed. Linear, proportional and angular measurements were compared among groups. Results: The sample was consisted of 25% of unpleasant, 55% of acceptable and 20% of pleasant according to subjective analysis.  In most measurements there were no differences among groups. Just in one linear measurement (sn-U1 FILS) significant statistical difference was observed. Group III has higher right and a left symmetry angel despite it has lower facial symmetry Conclusions: In the evaluation of facial measurements, it was observed that there were statistically non-significant except for the sn-U1 FILS, which is statistically significant. The photographic evaluations require more than one evaluator in different specialties to give more reliable judgment. The facial analysis influenced by, age, gender, cultural and racial factors.Keywords: Attractiveness, Facial esthetics, Facial analysis.